Efficacy of levetiracetam monotherapy in epilepsy associated with benign epileptiform discharges of childhood - N. A. Borovkova; A. G. Malov (Эпилепсия и пароксизмальные состояния, 2019)
Aim. To analyze efficacy of levetiracetam monotherapy in patients with epilepsy associated with benign epileptiform discharges of childhood (BEDC). Materials and methods. We examined 29 pediatric patients with idiopathic and symptomatic BEDC-associated epilepsy, including continuous spike-and-wave epileptiform activity during slow-wave sleep (CSWS) in the stage of clinical remission. Of those, 12 children received antiepileptic treatment with valproic acid, and 17 children received levetiracetam. The examination included passive awake EEG recordings (with functional tests) as well as daytime sleep EEG recordings (within 60 minutes). Results. Levetiracetam was no less efficient in monotherapy of BEDC-associated epilepsy (including the CSWS patterns) than the traditionally used valproic acid, especially in idiopathic forms of epilepsy. Conclusion. Levetiracetam can be recommended for the first-choice basic anti-epileptic monotherapy treatment.